2021
DOI: 10.32718/ujvas4-3.01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implant Suprelorin on cytological changes of vaginal epithelial cells in female dogs (4.7 mg deslorelin)

Abstract: Diagnosis of the estrous cycle in female dogs is important in veterinary medicine. The estrous cycle is divided into the following stages: proestrus, estrus, diestrus, metestrus, and anestrus, which due to the action of hormones, replace one after another. This feature of the estrous cycle leads to some difficulties with reproduction. It is hard to obtain newborns because of prolonged anestrus. Vaginal cytology is a simple and available diagnostic method of the estrous cycle. It is based on the analysis of vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
2
3
0
4
Order By: Relevance
“…In the present study, vaginal smears at the proestrus stage, showed a rise in the proportion of anuclated superficial cells and nucleated superficial cells, with a reduction in intermediate and parabasal cells. This observation is in agreement with the reports (Reddy et al, 2011;Holumbiyovska et al, 2021) for the dog and Sitaresmi et al (2019) in does. Also, the few numbers of parabasal and intermediate cells that were observed, is consistent with the findings of Sire-gar et al (2016); but these observations were at variance with that of Kustritz (2012), who reported very high proportions of intermediate cells and few nucleated superficial cells at proestrus stage.…”
Section: Vaginal Exfoliative Cytologysupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, vaginal smears at the proestrus stage, showed a rise in the proportion of anuclated superficial cells and nucleated superficial cells, with a reduction in intermediate and parabasal cells. This observation is in agreement with the reports (Reddy et al, 2011;Holumbiyovska et al, 2021) for the dog and Sitaresmi et al (2019) in does. Also, the few numbers of parabasal and intermediate cells that were observed, is consistent with the findings of Sire-gar et al (2016); but these observations were at variance with that of Kustritz (2012), who reported very high proportions of intermediate cells and few nucleated superficial cells at proestrus stage.…”
Section: Vaginal Exfoliative Cytologysupporting
confidence: 94%
“…The estrous cycle represents a complex neurohumoral process characterized by morphological and physiological changes in some of the reproductive organs, such as the vagina. These cyto-morphological changes in exfoliated cells in the vaginal smears, fairly reflect the underlying endocrine events of the reproductive cycle, due to sensitivity of vaginal epithelium to stimulation by sex hormones (Kinoshita et al, 2012;Peña-Corona et al, 2019;Holumbiyovska et al, 2021) and are, thus, considered as a better predictor of the breeding time.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Результати цитологічного дослідження епітелію піхви наведені у нашій попередній публікації (Holumbiyovska et al, 2021).…”
Section: матеріал і методи дослідженьunclassified
“…Також варто зазначити, що у окремих випадках цитологічна картина епітелію піхви може не вказувати на ознаки тічки. Цитологічно у дослідній групі фіксували прояви проеструсу починаючи з третьої доби після імплантації (Holumbiyovska et al, 2021), що не завжди було помітно у сук з контрольної групи. Детальні результати цитологічних змін епітелію піхви після застосування імпланту Супрелорін наведені в нашій попередній статті (Holumbiyovska et al, 2021).…”
Section: обговоренняunclassified